The abolition of man : or reflections on education with special reference to the teaching of English in the upper forms of schools - Lewis, Clive Staples, 1898-1963. (London, UK : Fount, 1999)
Includes bibliographical references.
First published 1943.
Keywords: Natural law -- criticism, interpretation, etc